Renewable Energy Revolution: A Review Of Innovative Strategies Towards Net Zero Emission (NZE) - Naibaho, Nathan Gorga Tona; Setyani, Atik; Pratomo, Dias Dibyo (Journal of Metallurgical Engineering and Processing Technology, 2025)
The Net Zero Emissions (NZE) program became a common term after the 2015 Paris Climate Agreement. This program aims to reduce environmental pollution that can cause global warming. Energy is one of the sectors that is the focus of the NZE program implementation efforts. The energy transition is a very important program, especially in relation to the NZE Program issue and mitigation of the Greenhouse Gas effect. The energy transition program must focus on reducing carbon intensity and providing more benefits to all households. Indonesia has committed to achieving NZE by 2060 or sooner. This study aims to examine the role of renewable energy in achieving the NZE program and analyze innovation strategies to accelerate the NZE program. This study uses a narrative literature review method to analyze information and literature. This study presents alternative solutions to the issue of renewable energy transition in realizing NZE. Utilization of abundant renewable energy to replace fossil fuels and also electrification of non-electricity sectors can be a priority solution in realizing NZE. In addition, the development of Carbon Capture, Utilization, Storage (CCUS), and Green Hydrogen technology is also very important for the industrial sector in mitigating the effects of greenhouse gases.